2018
DOI: 10.1302/1863-2548.12.180036
|View full text |Cite
|
Sign up to set email alerts
|

Submuscular plates versus flexible nails in preadolescent diaphyseal femur fractures

Abstract: Abstract:PurposeTo compare patient characteristics, operative time, estimated blood loss (EBL), postoperative length of hospital stay (LOS) and complications after insertion and removal of submuscular plates (SMPs) versus flexible nails (FNs) for paediatric diaphyseal femur fractures.MethodsWe reviewed records of 58 children (mean age, 7.7 years SD 2.0) with diaphyseal femur fractures who underwent treatment with SMPs (n = 30) or FNs (n = 28) from 2005 to 2017 (mean follow-up, 22 months SD 28). Patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…As plate fixation in general is not considered a treatment modality for this age group, we decided not to include this in our study either. Nevertheless, several studies found that IMN has better outcomes than plate fixation at young age [45][46][47][48][49][50].…”
Section: Results and Previous Literaturementioning
confidence: 99%
“…As plate fixation in general is not considered a treatment modality for this age group, we decided not to include this in our study either. Nevertheless, several studies found that IMN has better outcomes than plate fixation at young age [45][46][47][48][49][50].…”
Section: Results and Previous Literaturementioning
confidence: 99%
“…Enhanced biomechanical stability while simultaneously preserving fracture biology, especially in heavier children as well as in length unstable femur fractures has been highlighted as advantages of SMP over ESIN [11,[33][34][35]. However, bigger surgical exposure, larger volume of blood loss, longer hospital stay and difficulty encountered in implant removal are possible disadvantages [36].…”
Section: Discussionmentioning
confidence: 99%
“…15 Chen et al found that the use of FIN was associated with a shorter operative time, less blood loss and shorter length of hospitalisation compared to submuscular plating. 16 Concerns with antegrade nailing are that the blood supply to the femoral head may be compromised and that penetration through the greater trochanteric epiphysis may lead to epiphysiodesis and proximal femoral growth deformities. It is for these reasons that a retrograde approach, or antegrade approach with an entry port distal to the greater trochanteric epiphysis has been popularised with FIN insertion.…”
Section: Discussionmentioning
confidence: 99%